Doing Your Research Project: A Guide for First-time Researchers - Judith Bell; Stephen Waters (New York McGraw-Hill Education, 2018)
Step-by-step advice on completing an outstanding research project. This is the market-leading book for anyone doing a research project for the first time. Clear, concise and extremely readable, this bestselling resource provides a practical, step-by-step guide from initial concept through to completion of your final written research report. Thoroughly updated but retaining its well-loved style, this 6th edition provides: A brand new chapter describing the benefits of using social media in research, including how to use blogs, sharing ideas on research community sites, crowdsourcing, LinkedIn, Twitter and Facebook Tips on using online tools such as Delicious, Mendeley, Dropbox, EndNote and RefWorks to manage and organize your research Guidance on searching efficiently and effectively online using Google Scholar, Google Books and library databases and on correctly citing online sources Advice on creating online surveys for your research project, plus new material on using Skype and Google Hangouts for online interviewing To support your learning, each chapter contains introductory key points, "Dead End" boxes to warn of pitfalls, "Success" checklists and further reading sections. This practical, no-nonsense guide is vital reading for all those embarking on undergraduate or postgraduate study in any discipline, and for professionals in such fields as social science, education and health.
Keywords: Science; Academic; Research; Research methods; Research Methods (BIN2044-N)